A new species of Bedotia (Teleostei: Atherinomorpha: Bedotiidae) from the Rianila drainage of Eastern Madagascar, with redescriptions of Bedotia madagascariensis and Bedotia geayi - Loiselle, Paul V.; Rodriguez, Damaris (Zootaxa, 2007)
Bedotia madagascariensis Regan 1903, type species of the genus and  B. geayi Pellegrin 1907 are redescribed from recently collected topotypical material. The two species differ significantly with respect to their life colors, the lengths of the head, snout, caudal peduncle and bases of the second dorsal and anal fins as well as their second dorsal and anal fin ray counts. The aboriginal range of B. madagascariensis comprises eastward flowing streams from the Ivoloina River southward to Manambolo Creek inclusive of small streams flowing into the coastal lakes of the Pangalanes system situated between them, where it occurs up to an altitude of 30 m above sea level. A naturalized population is present in the westward-flowing Betsiboka drainage. Bedotia geayi is only known from the eastward-flowing Mananjary River, where it can be found in small streams between 300 m and 600 m above sea level. A second species of Bedotia  from the Rianila basin is described. Bedotia leucopteron sp. nov. is found in shaded streams between 100 m and 850 m above sea level.  The wide, iridescent white margins of the unpaired fins taken in combination with a melanophore pattern consisting of small, irregular black spots stochastically distributed over the flanks rather than a distinct midlateral band differentiate living individuals from all known congeners. Data on the natural history and conservation status of all three species are presented.